THE EFFECT OF PURPLE SWEET POTATO (Ipomoea batatas) FLOUR ON THE SQUID (Loligo sp.) NUGGET QUALITY - Alfian Arby; Desmelati '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was aimed to determine the effect of purple sweet potato flour on the squid nugget quality. The treatments were carried out in the mixture of tapioca flour and purple sweet potato flour to the total weight of used flour (175 grams), which consists of five levels; N0 (100% tapioca flour and 0% purple sweet potato flour), N1 (75% tapioca flour and 25% purple sweet potato flour), N2 (50% tapioca flour and 50% purple sweet potato flour), N3 (25% tapioca flour and 75% purple sweet potato flour), N4 (0% tapioca flour and 100% purple sweet potato flour). Based on this research, the effect of the purple sweet potato flour on the squid nugget quality was significantly effect to organoleptic value, moisture content, ash, carbohydrate, protein and fat content. The using of highest concentration of purple sweet potato was given the highest antioxidant activity. The results on the N2 was the best treatment with the characteristics of appearance such a thick purple, brilliant (8.17), very fragrant in odor, squid specific (7.29),2JOM: FEBRUARI 2015savory flavor (8.33) and dense texture, compact (8.39), moisture content 58.68%, ash content 1.67%, carbohydrate content 17.47%, protein content 19.66%, fat content 0.62% and antioxidant activity 8.049 mg/mL.Keywords: Tapioca flour, sweet potato flour, nuggets squid, antioxidant